Expulser les étrangers de la monarchie hispanique : un sujet épineux (1591-1625) - Guillaume Gaudin (Les Cahiers de Framespa)
Shortly after the «Discovery of America», the Catholic Kings issued a ban for foreigners to cross the Atlantic and settle in the West Indies. In this composite monarchy, the definition of «naturaleza» was not easy and, for a long time, it was not possible for foreigners to obtain citizenship by integration. In 1591, Felipe II asked the Hispano-American authorities to expel foreigners, while allowing them, at the same time, to stay given the payment of a fee (the «composición»). From 1591 to 1625 several campaigns of expulsion and «composición» were undertaken in the «audiencias». The discourse of the authorities changed from a recognition of foreign qualifications to xenophobia. Foreign control increased around 1615 and deportations were carried out.